If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 8) + -2x = 60 Reorder the terms: 5(8 + x) + -2x = 60 (8 * 5 + x * 5) + -2x = 60 (40 + 5x) + -2x = 60 Combine like terms: 5x + -2x = 3x 40 + 3x = 60 Solving 40 + 3x = 60 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + 3x = 60 + -40 Combine like terms: 40 + -40 = 0 0 + 3x = 60 + -40 3x = 60 + -40 Combine like terms: 60 + -40 = 20 3x = 20 Divide each side by '3'. x = 6.666666667 Simplifying x = 6.666666667
| 3x+10-6=7 | | 10=-3F+10N | | (x+3)-27=30 | | 26+13x=12(x+2) | | -2+2=0+2 | | 2x-6=-x+2 | | 6x+11=8x+15 | | 5=4F-5N | | 3(a-1)+2(6+2a)=8a-6-5+a | | 5k-9/4=k | | -9-5k=-24 | | 3x+2+y=22 | | c-22=-27 | | 48x+6=246 | | y=x^2+12+35 | | 5-3x=4x+12 | | 6-3A+5B=0 | | (-9x+11)8= | | 3z^3+6z^2=72z | | 1/3X-1-1/4X+2=3 | | 23=11x+1 | | 9=-2x+4 | | 7(p+1)=p-9 | | C=3.14(5) | | -5/6f+1=-4 | | 12-2A-2B=0 | | 5+-26=18x | | 2=15x | | (x+8)(x-3)+30=0 | | 52=4x-4 | | -4/6f+1=-4 | | 7u+9u+u=140 |